Computer-delivered and web-based interventions to improve depression, anxiety, and psychological well-being of university students: a systematic review and meta-analysis - Davies, E. Bethan; Morriss, Richard K.; Glazebrook, Cris (2015)
Background: Depression and anxiety are common mental health difficulties experienced by university students and can impair academic and social functioning. Students are limited in seeking help from professionals. As university students are highly connected to digital technologies, Web-based and computer-delivered interventions could be used to improve students’ mental health. The effectiveness of these intervention types requires investigation to identify whether these are viable prevention strategies for university students.